Dental school Special Patient Care Program during 1977-1979 and 1987-1989: comparisons of regional and state disabled populations - Jedrychowski, J R; Lindemann, R (Special care in dentistry, 1991)
New patients referred to the Special Patient Care Program at UCLA School of Dentistry during the period of 1977-1979 were compared with new patients referred during the period of 1987-1989. Parameters measured were age, gender, geographic distance from the treatment facility, and primary disability. The UCLA profile of disabilities was then compared with local, regional, and state data on disabilities. The mean patient age decreased from 47 years of age in 1977-1979 to 34 years in 1987-1989 while gender distribution remained approximately the same. The distance from patient's residence to the dental treatment facility increased from the 1977-1979 period to the 1987-1989 period with more new patients traveling over 5 miles for treatment. The 1987-1989 special patient care new patient population was highly representative when disability type was compared with a juvenile population (less than 21 years of age) from the five Regional Centers in LA County and the LA County and State of California Department of Developmental Disabilities populations. The patient training base of an undergraduate dental school program for persons with disabilities is representative of the disabled population of LA county and the state of California.